Social Economy Media Podcast Bocor Alus Politik: The Role of the Market in Expanding Business Volume Tempo - Makroen Sanjaya; Nurlaila Sari Amallah; Kristina Nurhayati; Fitri Sarasati (Jurnal Mamangan, 2025)
As Tempo Magazine’s print circulation declined and audiences increasingly turned to digital platforms, the company explored new formats for delivering journalism. One such innovation is the Bocor Alus Politik podcast, which offers more dynamic and accessible content. Ideally, media organizations should continue to serve as watchdogs while also seeks alternative revenue models to reduce dependence on advertising. This study focus on how the Bocor Alus Politik podcast leverages market forces to support Tempo’s business growth and address existing gaps in the literature. Adopting a qualitative method within a constructivist paradigm, the research draws on observations, analysis of YouTube content, and interviews with Tempo’s senior management and the main podcast host. Findings suggest that the podcast has significantly broadened Tempo’s reach—especially to regions previously unreachable by the print edition—and has contributed to growth in digital subscriptions and public engagement through stock ownership, particularly among millennials. Bocor Alus Politik represents Tempo’s strategic response to shifts in media consumption habits. Future studies on media economics should focus on geographic markets and the factors that shape the podcasting sector to gain a deeper understanding of these developments.